MicroRNA‐107 protects against inflammation and endoplasmic reticulum stress of vascular endothelial cells via KRT1‐dependent Notch signaling pathway in a mouse model of coronary atherosclerosis. Issue 7 (12th December 2018) - Gao, Zhi‐Feng; Ji, Xiao‐Lin; Gu, Jie; Wang, Xiao‐Yu; Ding, Lin; Zhang, Huan
Abstract: Coronary atherosclerosis is a long‐term, sustained, and evolving inflammatory disease manifested with the remodeling of the coronary arteries. The purpose of this study is to explore the potential role of microRNA‐107 (miR‐107) in vascular endothelial cells (VECs) in coronary atherosclerosis by regulating the KRT1 gene and the Notch signaling pathway. A mouse model of coronary atherosclerosis was established. The relationship between miR‐107 and KRT1 was analyzed and verified by dual‐luciferase reporter assay. The functional role of miR‐107 in coronary atherosclerosis was determined using ectopic expression and depletion. Blood lipid levels and atherosclerotic index (AI) were measured in atherosclerotic mice. Expression pattern of miR‐107, KRT1, Notch signaling pathway, inflammatory/anti‐inflammatory factors, and endoplasmic reticulum (ER) stress‐related genes was evaluated by means of reverse transcription quantitative polymerase chain reaction, western blot analysis, and enzyme‐linked immunosorbent assay. Meanwhile, cell‐cycle distribution and cell apoptosis in VECs were assessed by flow cytometry. Atherosclerotic mice exhibited higher blood lipid levels, AI, apoptotic index, and KRT1‐positive expression as well as inhibited Notch signaling pathway when compared with normal mice. The miR‐107 was revealed to bind to KRT1; miR‐107 upregulation or KRT1 silencing resulted in reductions in blood lipid levels and AI, inhibition in cell apoptosis, inflammation, and ER stress. Restored miR‐107 or downregulated KRT1 activated the Notch signaling pathway. These results supported the notion that miR‐107‐targeted KRT1 inhibition activated the Notch pathway, thereby, protecting against the coronary atherosclerosis. Findings in this study might provide a novel biomarker for the coronary atherosclerosis treatment. Abstract : These results supported the notion that miR‐107‐targeted KRT1 inhibition activated Notch pathway, thereby, protecting against coronary atherosclerosis. Findings in this study might provide a novel biomarker for coronary atherosclerosis treatment.